THE IMPLEMENTATION OF TAI TYPE COOPERATIVE LEARNING WITH PEER TUTOR TO IMPROVE STUDENTS’ ACHIEVEMENT ON INDONESIAN LANGUAGE - Yuliastini, Nyoman Setori (Universitas Pendidikan Ganesha, 2017)
This present study aims at improving students’ achievement in Indonesian language through tai type cooperative learning with peer tutor in the academic year of 2015/2016. This study is a classroom action research and takes place at SMPN 1 Seririt from September to November 2015. It undergoes preliminary study to the action. A total number of 34 students consist of 16 female and 18 male are purposefully selected as the sample of this study. The researcher focuses on the evaluation on the first cycle and the second cycle after implementing technique. This study results in finding out that tai type cooperative learning with peer tutor has successfully improved students’ achievement on Indonesian language in the academic year of 2015/2016. This is reflected by the improvement of the students’ score with 85.29% of them have fulfilled the criteria of success in the first cycle. Nonetheless, there are 94.12% students who passed the criteria of success.